INCENP–aurora B interactions modulate kinase activity and chromosome passenger complex localization - Xu, Zhenjie (The Rockefeller University Press, 2009)
Dynamic localization of the chromosomal passenger complex (CPC) during mitosis is essential for its diverse functions. CPC targeting to centromeres involves interactions between Survivin, Borealin, and the inner centromere protein (CENP [INCENP]) N terminus. In this study, we investigate how interactions between the INCENP C terminus and aurora B set the level of kinase activity. Low levels of kinase activity, seen in INCENP-depleted cells or in cells expressing a mutant INCENP that cannot bind aurora B, are sufficient for a spindle checkpoint response when microtubules are absent but not against low dose taxol. Intermediate kinase activity levels obtained with an INCENP mutant that binds aurora B but cannot fully activate it are sufficient for a robust response against taxol, but cannot trigger CPC transfer from the chromosomes to the anaphase spindle midzone. This transfer requires significantly higher levels of aurora B activity. These experiments reveal that INCENP interactions with aurora B in vivo modulate the level of kinase activity, thus regulating CPC localization and functions during mitosis.